Nature-Based Solutions for Restoration of Ecosystems and Sustainable Urban Development - Panagopoulos, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume examines the applicability of nature-based solutions in ecological restoration practice and in contemporary landscape architecture by bringing together ecology and architecture in the built environment. Green infrastructure is used to address urban challenges such as climate change adaptation, disaster risk reduction, and stormwater management. In addition, thermal comfort nature-based solutions reintroduce critical connections between natural and urban systems. In light of ongoing developments in sustainable urban development, the goal is a paradigm shift towards a landscape that restores and rehabilitates urban ecosystems. The ten contributions to this book examine a wide range of successful cases of designing healthier, greener and more resilient landscapes in different geographical contexts, from the United States of America and Brazil, through various European regions, to Singapore and China. While some chapters attempt to conceptualize the interconnections between cities and nature, others clearly have an empirical focus. Therefore, this volume provides a rich body of work and acts as a starting point for further studies on restoration of ecosystems and integrative policies such as the United Nations Sustainable Development Goals.